The Nexus between Economic Freedom and Economic Growth in the LDCs. An Empirical Analysis for the Period 2000-2021 - António Afonso; M. Carmen Blanco-Arana (Center for Economic Studies and ifo Institute (CESifo), 2023)
Economic freedom and economic growth can be connected in most countries, but it is often necessary to specify those aspects of economic freedom that can foster economic growth. This paper examines the nexus between economic freedom and economic growth in the Least Developed Countries (LDCs) using panel data for the period 2000-2021. Results show that, in general, economic freedom positively influences economic growth in the LDCs. Moreover, most economic freedom factors raise economic growth. However, the effect of government spending, fiscal and financial freedom on economic growth is negative. Using a Principal Component Analysis for the economic freedom sub-indicators confirms the results.
Keywords: C23; G10; O10; O43; 330; economic freedom; economic growth; LDCs; financial development; panel data